Legal Application of the Right to Data Portability In Peer To Peer Lending in Indonesia - Setianto, Ori; Agusta, Hendrawan; Nadya, Annisa Putri; Siahaan, Rudy; Firanda, Gika Asdina (Universitas Negeri Gorontalo, 2020)
Once Personal Data entered into an Electronic System has become Electronic Information in digital form. It can be seen using parameters that the Personal Data is no longer in atom base format but has changed to byte base format. Electronic Information in IT Law approach can be transmitted between Electronic Systems in a possible connection. Data Portability arise, one of which is to allow Data Subject as the Application User to transmit his Personal Data from one Electronic System to another for his own benefit, with the consent and or request of the Data Subject. The development of Data Portability is influenced by the European Union through the General Data Protection Regulation (GDPR), where this is one of the factors that must be considered along with the development of Data is The New Oil phenomenon. P2P Lending business model as a part of Financial Technology (Fintech) in the registration process for Lending accounts is also related to Data Portability. This journal discusses on how the application of The Right to Data Portability in P2P Lending in Indonesia.